Anti-Tumor Potency of Short-Term Interleukin-15 Dendritic Cells Is Potentiated by In Situ Silencing of Programmed-Death Ligands - Versteven, Maarten; Flumens, Donovan; Campillo-Davó, Diana; De Reu, Hans; Van Bruggen, Laura; Peeters, Stefanie; Van Tendeloo, Viggo; Berneman, Zwi; Dolstra, Harry; Anguille, Sébastien; Hobo, Willemijn; Smits, Evelien; et al. (Frontiers in Immunology, 2022)
Dendritic cell (DC) vaccines have proven to be a valuable tool in cancer immune therapy. With several DC vaccines being currently tested in clinical trials, knowledge about their therapeutic value has been significantly increased in the past decade. Despite their established safety, it has become clear that objective clinical responses are not yet robust enough, requiring further optimization. Improvements of this advanced therapy medicinal product encompass, among others, regulating their immune stimulating capacity by in situ gene engineering, in addition to their implementation in combination therapy regimens. Previously, we have reported on a superior monocyte-derived DC preparation, including interleukin-15, pro-inflammatory cytokines and immunological danger signals in the culture process. These so-called IL-15 DCs have already proven to exhibit several favorable properties as cancer vaccine. Evolving research into mechanisms that could further modulate the immune response towards cancer, points to programmed death-1 as an important player that dampens anti-tumor immunity. Aiming at leveraging the immunogenicity of DC vaccines, we hypothesized that additional implementation of the inhibitory immune checkpoint molecules programmed death-ligand (PD-L)1 and PD-L2 in IL-15 DC vaccines would exhibit superior stimulatory potential. In this paper, we successfully implemented PD-L silencing at the monocyte stage in the 3-day IL-15 DC culture protocol resulting in substantial downregulation of both PD-L1 and PD-L2 to levels below 30%. Additionally, we validated that these DCs retain their specific characteristics, both at the level of phenotype and interferon gamma secretion. Evaluating their functional characteristics, we demonstrate that PD-L silencing does not affect the capacity to induce allogeneic proliferation. Ultimately designed to induce a durable tumor antigen-specific immune response, PD-L silenced IL-15 DCs were capable of surpassing PD-1-mediated inhibition by antigen-specific T cells. Further corroborating the superior potency of short-term IL-15 DCs, the combination of immune stimulatory components during DC differentiation and maturation with in situ checkpoint inhibition supports further clinical translation.